Development of proof loading method for railway bridges with masonry abutments - Wang, Chao; Gonzalez-Libreros, Jaime; Elfgren, Lennart; Sas, Gabriel; Daescu, Cosmin; Enochsson, Ola; Höjsten, Tommy (Luleå tekniska universitet, Byggkonstruktion och brand, 2024)
Railway bridges with masonry abutments represent a significant portion of aging infrastructure in north Sweden. The assessment of their structural integrity is crucial to ensure safe and efficient railway operations. This paper presents the development of a proof loading method tailored specifically for railway bridges with masonry abuments. Before conducting the tests, the bridge condition was assessed through visual inspections using ground-based photogrammetry and Ground Penetration Radar (GPR). Realistic loads were simulated using a carefully chosen train fleet during the tests to evaluate load-carrying capacity and structural integrity. Comprehensive data, including strains, displacements, temperature, and acceleration measurements, were collected to gain insights into the bridges' behavior under real-life loading conditions. This data played a crucial role in making predictions and guiding maintenance decisions for targeted rehabilitation efforts. To enhance capacity assessments, finite element models were calibrated using test results, enabling predictions of how the bridges would respond to varioius loads. Full text license: CC BY-NC-ND; ISBN for host publication: 978-1-032-77040-6, 978-1-032-77560-9, 978-1-003-48375-5